2022
DOI: 10.3758/s13421-022-01316-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of facial occlusion on facial impressions of trustworthiness and dominance

Abstract: Recognizing the role that facial appearance plays in guiding social interactions, here we investigated how occlusions of the bottom-face region affect facial impressions of trustworthiness and dominance. Previous studies suggesting that different facial features impact inferences on these traits sustain the hypothesis that wearing a face mask will differently affect each trait inference. And specifically, that trustworthiness impressions will be more disrupted by this type of face occlusion than dominance impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
3
4
1
Order By: Relevance
“…Results showed that regardless of base attractiveness, unoccluded faces had higher perceived trustworthiness than faces wearing face masks. The predictions were not supported, and the results of this study were inconsistent with those of many previous studies [ 18 21 , 50 , 51 ]. Additionally, the prediction that Japanese people wear face masks because conformity to social norms is a top priority [ 35 ] and that this behavior is linked to higher trustworthiness was not supported.…”
Section: Discussioncontrasting
confidence: 99%
“…Results showed that regardless of base attractiveness, unoccluded faces had higher perceived trustworthiness than faces wearing face masks. The predictions were not supported, and the results of this study were inconsistent with those of many previous studies [ 18 21 , 50 , 51 ]. Additionally, the prediction that Japanese people wear face masks because conformity to social norms is a top priority [ 35 ] and that this behavior is linked to higher trustworthiness was not supported.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings indicated that the absence of upper facial features is expected to have a negative impact on trust-related behaviors and expectations. A Previous study using high and low trustworthy faces has similar findings (Oliveira & Garcia-Marques, 2022 ). The discriminability between the perceived trustworthiness of trustworthy and untrustworthy faces was higher when only their top halves were visible compared to when only their bottom halves were visible (Oliveira & Garcia-Marques, 2022 ).…”
Section: Discussionsupporting
confidence: 76%
“…This might be due to the intermediate strength of the initial trustworthiness of the faces. Previous studies have found that the impact of masks varies depending on the initial trustworthiness of the faces (Marini et al, 2021 ; Oldmeadow & Koch, 2021 ; Oliveira & Garcia-Marques, 2022 ). Therefore, in Experiment 3, we expanded the range of initial facial trustworthiness, choosing faces with low, moderate, and high initial trustworthiness as our experimental materials.…”
Section: Methodsmentioning
confidence: 99%
“…This was an expected result since previous studies suggested that these judgments rely primarily on structural cues such as eyes-to-eyebrow distance and width-to-height ratio (Costa et al, 2017 ; Vernon et al, 2014 ), areas not affected using masks. Previous studies have also shown dominance impressions were less affected by masking than trustworthiness impressions (Oliveira & Garcia-Marques, 2022 ).…”
Section: Discussionmentioning
confidence: 73%